Metformin Regulates TET2 Expression to Inhibit Endometrial Carcinoma Proliferation: A New Mechanism - Zhang, Jingbo; Kuang, Lei; Li, Yanyu; Wang, Qing; Xu, Hui; Liu, Jianwei; Zhou, Xueyan; Li, Yang; Zhang, Bei (Frontiers in Oncology, 2022)
Objectives To investigate the relationship between TET2 expression and endometrial cancer’s clinicopathological features and prognosis, and the effect of metformin on TET2 and 5hmC levels in endometrial cancer cells. Methods The clinical significance of TET2 expression in endometrial carcinoma was analyzed from TCGA public database. Eighty-eight patients with endometrial cancer and 20 patients with normal proliferative endometrium were enrolled in this study. TET2 and 5hmC were respectively detected by Immunohistochemistry and ELISA in endometrial tissues. Kaplan-Meier and Cox proportional hazard regression models were used to analyze relationships between TET2 and 5hmC and the overall survival of EC patients. Endometrial cell proliferation was assessed after TET2 gene knockdown. Western blotting and real-time PCR were used to detect the effect of metformin on TET2 expression and to explore whether AMPK is involved in metformin-mediated TET2 regulation. Results The clinical significance of expression of TET2 in endometrial cancer from TCGA public database confirmed that TET2 expression was significantly down-regulated in cancer samples and TET2 expression was also significantly different among different histopathological samples and TET2 is down-regulated in advanced, high-grade, and relapsed endometrial carcinoma tissues(P<0.05). Immunohistochemical analysis showed that TET2 and 5hmC levels were significantly lower in endometrial adenocarcinoma(P<0.05). TET2 expression was correlated with the degree of EC differentiation (P < 0.05). 5hmC levels were associated with clinical stage, differentiation, the depth of myometrial invasion, and lymph node metastasis (P < 0.05). The mean survival time of patients with negative staining for TET2 and 5hmC was shorter than that of patients with positive staining for both markers (P<0.05). Multivariate Cox regression analysis showed that TET2 expression was an independent risk factor for prognosis in patients with endometrial adenocarcinoma (HR = 14.520, 95% CI was 1.From 060 to 198.843, P = 0.045). siRNA-mediated TET2 knockdown increased the proliferation of EC cells. Metformin increased the levels of TET2 and 5hmC in EC cells. AMPK was involved in the regulation of TET2 by metformin. Conclusions TET2 may play an important role in EC development and may be a prognostic marker. Moreover, TET2 may be involved in a novel mechanism by which metformin inhibits EC cell proliferation.